What investors fear most during COVID-19 Pandemic: country-level versus global level of growth in cases and fatalities? / Hamdan Amer Ali Al-Jaifi … [et al.] - Amer Ali Al-Jaifi, Hamdan; Najaf, Khakan; Hussein Al-Rassas, Ahmed; Kaur, Harpaljit (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This study examined the impact of Covid-19 confirmed cases and fatalities on the investors’ fear of the equity markets during the COVID-19 pandemic. In this study, daily data of COVID-19 confirmed cases and fatalities over 51 countries across the world were collected. Besides, the spread between high and low prices on the major indices of these countries was used to capture the level of investor’s fear on a daily basis. The findings showed that investors’ fear level increases due to the high growth of confirmed cases and fatalities at the country level. However, investors are reacting positively to the global expansion of confirmed cases and deaths. Besides, the study found that investors reacted proactively towards confirmed cases versus deaths. These findings imply that investors’ perception of the country and global trends of the COVID-19 pandemic is different as investors are getting more worried about the upward country-level trends and getting more confident from the global upward trends. These findings imply that the stock markets might be rising due to certain global vital economies' monetary policy and recovery actions. To the best of our knowledge, this study is the first to provide evidence on the investor’s fear arising from COVID-19 confirmed cases and fatalities domestically and globally.